Antitumor effect and toxicity of free rhodium (II) citrate and rhodium (II) citrate-loaded maghemite nanoparticles in mice bearing breast cancer - Carneiro, Marcella Lemos Brettas (BioMed Central, 2013)
BACKGROUND: Magnetic fluids containing superparamagnetic iron oxide nanoparticles represent an attractive platform as nanocarriers in chemotherapy. Recently, we developed a formulation of maghemite nanoparticles coated with rhodium (II) citrate, which resulted in in vitro cytotoxicity enhanced up to 4.6 times when compared to free rhodium (II) citrate formulation on breast carcinoma cells. In this work, we evaluate the antitumor activity and toxicity induced by these formulations in Balb/c mice bearing orthotopic 4T1 breast carcinoma. METHODS: Mice were evaluated with regard to the treatments’ toxicity through analyses of hemogram, serum levels of alanine aminotransferase, iron, and creatinine; DNA fragmentation and cell cycle of bone marrow cells; and liver, kidney and lung histology. In addition, the antitumor activity of rhodium (II) citrate and maghemite nanoparticles coated with rhodium (II) citrate was verified by tumor volume reduction, histology and immunohistochemistry. RESULTS: Regarding the treatments’ toxicity, no experimental groups had alterations in levels of serum ALT or creatinine, and this suggestion was corroborated by the histopathologic examination of liver and kidney of mice. Moreover, DNA fragmentation frequency of bone marrow cells was lower than 15% in all experimental groups. On the other hand, the complexes rhodium (II) citrate-functionalized maghemite and free rhodium (II) citrate led to a marked growth inhibition of tumor and decrease in CD31 and Ki-67 staining. CONCLUSIONS: In summary, we demonstrated that both rhodium (II) citrate and maghemite nanoparticles coated with rhodium (II) citrate formulations exhibited antitumor effects against 4T1 metastatic breast cancer cell line following intratumoral administration. This antitumor effect was followed by inhibition of both cell proliferation and microvascularization and by tumor tissue injury characterized as necrosis and fibrosis. Remarkably, this is the first published report demonstrating the therapeutic efficacy of maghemite nanoparticles coated with rhodium (II) citrate. This treatment prolonged the survival period of treated mice without inducing apparent systemic toxicity, which strengthens its use for future breast cancer therapeutic applications.